CEDS Alumni Engagement System - Hazinol, Muhamad Hazrin Hakim; Misri, Muhamad Idzhar; Asraf Redhuwan, Nur Asrina; Mariam Abdul Hamid, (Multidisciplinary Applied Research and Innovation, 2024)
Alumni are the individuals who represent the university outside of the educational environment. Alumni now play an important role for all current students and their university. From the study, UTHM Diploma Study Centre (CEDS) do not have any suitable channel for them to collect, update and manage all their information regarding alumni data. This project offers a solution, which is to develop an alumni website in order to ensure that the institution can retain the relationship that benefits both of them. The parties involved in this project are alumni of CEDS alumni. The system contains several internal functions that meet the needs of alumni such as creating an alumni account, viewing information and updating the system, following alumni activities, searching and viewing alumni members. The study uses the Waterfall method which acts as a guideline throughout the development of this project. This project was developed using Hypertext Markup Language (HTML), Cascading Style Sheets (CSS), Javascript, and Hypertext Processor (PHP) as well as MySQL for the database. Visual Studio version 1.79.2 is used as a software that generates the codes to control overall programmes and build the interface for users to interact. After the testing was conducted, all of the components and software have reacted as intended which produces the desired result which is the CEDS Alumni Engagement System.This project choose Universiti Teknologi Mara (UiTM) as benchmarking for the alumni systems development  to get more knowledge and information about what the alumni system usually have. After the project was completed, all of the goals were achieved, and the outcomes complied with the objectives.